Prehistoric Rain Cookies: Geological-Inspired Culinary Creation Promoting Local Socio-Cultural and Economic Empowerment - Dina Tania; Herry Riswandi (Universitas Muhammadiyah Sidoarjo, 2023)
This scientific article presents the development and implementation of a community engagement project centered around the creation of